Site‐Selective Tertiary Alkyl–Fluorine Bond Formation from α‐Bromoamides Using a Copper/CsF Catalyst System. (10th June 2016) - Nishikata, Takashi; Ishida, Syo; Fujimoto, Ryo
Abstract: A copper‐catalyzed site‐selective fluorination of α‐bromoamides possessing multiple reaction sites, such as primary and secondary alkyl−Br bonds, using inexpensive CsF is reported. Tertiary alkyl−F bonds, which are very difficult to synthesize, can be formed by this fluorination reaction with the aid of an amide group. Control experiments revealed that in situ generated CuF2 is a key fluorinating reagent that reacts with the tertiary alkyl radicals generated by the reaction between an α‐bromocarbonyl compound and a copper(I) salt.